Bdh2 Deficiency Promotes Endoderm-Biased Early Differentiation of Mouse Embryonic Stem Cells - Fu, Yuting; Liu, Fangyuan; Cao, Shuo; Zhang, Jia; Wang, Huizhi; Wu, Baojiang; Song, Yongli; Duo, Shuguang; Li, Xihe; Bao, Siqin (Frontiers in Cell and Developmental Biology, 2021)
3-hydroxybutyrate dehydrogenase-2 (Bdh2), a short-chain dehydrogenase, catalyzes a rate-limiting step in the biogenesis of the mammalian siderophore, playing a key role in iron homeostasis, energy metabolism and apoptosis. However, the function of Bdh2 in embryonic stem cells (ESCs) remains unknown. To gain insights into the role of Bdh2 on pluripotency and cell fate decisions of mouse ESCs, we generated Bdh2 homozygous knockout lines for both mouse ASC and ESC using CRISPR/Cas9 genome editing technology. Bdh2 deficiency in both ASCs and ESCs had no effect on expression of core pluripotent transcription factors and alkaline phosphatase activity, suggesting dispensability of Bdh2 for self-renewal and pluripotency of ESCs. Interestingly, cells with Bdh2 deficiency exhibited potency of endoderm differentiation in vitro; with upregulated endoderm associated genes revealed by RNA-seq and RT-qPCR. We further demonstrate that Bdh2 loss inhibited expression of multiple methyltransferases (DNMTs) at both RNA and protein level, suggesting that Bdh2 may be essentially required to maintain DNA methylation in ASCs and ESCs. Overall, this study provides valuable data and resources for understanding how Bdh2 regulate earliest cell fate decision and DNA methylation in ASCs/ESCs.